Model Prediksi Financial Distress Grup Perusahaan Keluarga Di Indonesia Dengan Model Beneish Ratio Index - Nurina Prawinin Tyas; Nurmala Ahmar; M. Ardiansyah Syam (Jurnal Riset Akuntansi & Perpajakan (JRAP), 2020)
ABSTRACT This study aims to test and prove the empirical evidence of the Financial Distress Prediction Model of Family Companies in Indonesia with the Beneish Ratio Index. The sample used in this study is a group of family companies in Indonesia which are listed on the Indonesia Stock Exchange with an observation period of 31 December 2014 to 2018. The research method used is a quantitative method with a survey approach for secondary data. The Days Sales in Receivable Index (DSRI), Sales Growth Index (SGI), Sales General and Administrative Index (SGAI), and Leverage Index (LVGI) variables do not differ in the treatment of the Beneish Model components based on the Financial Distress status of the Family Group Company. Variable Gross Margin Index (GMI), Asset Quality Index (AQI), Depreciation Index (DEPI), and Total Accruals to Total Assets Index (TATA) differ in the treatment of the Beneish Model component based on the Financial Distress status of the Family Company Group. This research contributes to the parties concerned with the prediction of financial distress, such as auditors and the government in assessing the potential for financial distress in the company. ABSTRAK Studi ini bertujuan untuk menguji dan membuktikan bukti empiris Model Prediksi Financial Distress Grup Perusahaan Keluarga Di Indonesia Dengan Beneish Ratio Index. Sampel yang digunakan dalam penelitian ini adalah Grup perusahaan keluarga di Indonesia yang terdaftar di Bursa Efek Indonesia dengan periode pengamatan 31 Desember 2014 hingga 2018. Metode penelitian yang digunakan adalah metode kuantitatif dengan pendekatan survey untuk data sekunder. Variabel Days Sales in Receivable Index (DSRI), Sales Growth Index (SGI), Sales General and Administrative Index (SGAI), dan Leverage Index (LVGI) tidak ada perbedaan perlakuan komponen Beneish Model berdasarkan status Financial Distress pada Grup Perusahaan Keluarga. Variabel Gross Margin Index (GMI), Asset Quality Index (AQI), Depreciation Index (DEPI), dan Total Accruals to Total Assets Index (TATA) ada perbedaan perlakuan komponen Beneish Model berdasarkan status financial distress pada Grup Perusahaan Keluarga. Riset ini memberikan panduan kepada pihak-pihak yang berkepentingan terhadap memprediksi financial distress yang akan terjadi dalam perusahaan ataupun industri, pihak yang berkepentingan seperti Auditor dan Pemerintahan. JEL Classification : G32, M41